1984
DOI: 10.1038/hdy.1984.20
|View full text |Cite
|
Sign up to set email alerts
|

The ecological genetics of the speckled wood butterfly, Pararge aegeria L.—A preliminary study

Abstract: SUMMARYPhenologic and geographic variation in background colouration and hind wing spotting in the Satyrid butterfly Pararge aegeria are described from a study of cabinet specimens. This species has two generations in the year. The spring generation exhibits a bimodal pattern of emergence: those individuals which overwinter as pupae emerging earlier than those which pass the winter in the larval state. These early and late spring broods exhibit statistical phenotypic differences which seem to become obscured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Henriksen & Kreutzer 1982; Emmet & Heath 1989): females are larger (heavier) and have larger pale patches on the dorsal wing surface. No difference in relative eyespot size was found and Packer (1984) also showed that there is no difference between the sexes in the number of spots. This is in contrast to spot characteristics in some other satyrine butterflies, where the sexes were found to differ in both number of spots and size of particular spots (e.g.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Henriksen & Kreutzer 1982; Emmet & Heath 1989): females are larger (heavier) and have larger pale patches on the dorsal wing surface. No difference in relative eyespot size was found and Packer (1984) also showed that there is no difference between the sexes in the number of spots. This is in contrast to spot characteristics in some other satyrine butterflies, where the sexes were found to differ in both number of spots and size of particular spots (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…On the dorsal wing surface, speckled woods have a pattern of yellow patches scattered in the brown wing colour, and a series of three or four (rarely two) submarginal eyespots. Seasonal and geographical variation in these features has been studied in collection specimens of the U.K. by Packer (1984). These small eyespots are considered to be predator‐deflecting devices (Blest 1957), but there is little direct evidence available.…”
Section: Introductionmentioning
confidence: 79%
“…It results in a bimodal emergence pattern for the spring generation, whereas their directly developing offspring form a largely overlapping cohort as a second or summer generation. Using a compilation of collection specimens, Packer (1984) found that early spring P. aegeria have paler dorsal wing colour than late‐spring individuals. Shreeve (1992) reports less dorsal melanization of basal wing area in summer broods.…”
Section: Methodsmentioning
confidence: 99%